Clean production strategies adoption: A survey on food and beverage manufacturing sector - Abidin, Rahimi; Abdullah, Che Sobry; Osman, Wan Nadzri (IBIMA Publishing, 2010)
Clean production strategies are the continuous application of an integrated, preventive environmental strategies applied to process, products and services to increase overall efficiency and reduce risks to humans and the environment.This paper provides an analysis of factors influencing the adoption of clean production strategies among food and beverage firms in Peninsular Malaysia. The main purpose is to determine the relationships of three non regulatory factors with clean production strategies adoption. Three sets of interrelated factors leading to the widespread adoption of these technologies considered are: technology characteristics, technology performances and communication networks.This paper begins with an introduction and literature review, followed by the hypotheses statements. Pearson Correlation analysis was applied to examine these hypotheses. A sample of 76 Malaysian food and beverage firms was used for investigation, with one respondent for each firm. The results of the analysis indicated that technology characteristics, technology performances and communication networks are significantly influence the adoption of clean production strategies.